Memory for Max, Claire, Ida and company - Carli, Robert 1970- (<<The>> Criterion collection, 2010)
"Elderly residents of a Toronto nursing home cope with loss, loneliness and other heartbreaking challenges of growing old, as the home's staff work tirelessly to provide an environment of dignified, compassionate care." [imdb.com]
Original: Kanada 2005
Bildformat 1.78:1 (16:9)
Keywords: Alter; Senile Demenz; Altenpflegeheim; Toronto; Film; DVD-Video